Study on an effective integrated model of Ka-band mobile satellite channel - Juan WEI; Da LIU; Gang-qi TIAN (Tongxin xuebao)
In order to describe the Ka-band mobile satellite communications channel fading features more realitically,a mobile satellite integrated channel model was proposed.The characteristics of the mobile satellite propogation channel were analysed in detail.Weather conditions,as well as multi-path fading and shadowing were taken into account as main influencing factors.On this basis,airspace channel model was built obeying the Gaussian distribution as well ground surface,which obey Rice,Rayleigh and Lognormal joint distribution.Then the integrated channel model was presented considering weather effects on condition that the two parts are independent each other in the influence of the channel characteristics.The mathematical analysis model and simulation model of the new integrated channel model were established respectively.Finally,the BER(bit error rate)performance was analyzed for different weather conditions and shadows.Compared with the theoretical BER,the integrated channel model in satellite mobile communication systems is correct and reasonable.